Identify Direct Lightning Strike Location Based on Discrete Wavelet Transform for 115-kV Transmission System - Chiradeja, Pathomthat; Ngaopitakkul, Atthapol (My University, 2022)
This paper proposes three techniques for locating lightning strikes in a 115 kV transmission system over 88.5 km, based on the arrival time of a transient wave obtained from a discrete wavelet transform (DWT). The first technique calculates the location based on the 'type D' travelling wave method. The second technique analyses the first arrival time and same reflected-back wave arrival time between two substations. In the third technique, two sensors are installed to record arrival times at each sensor. Case studies of direct lightning strikes to phase conductors (shielding failure) are simulated using the 'Alternative Transients Program/Electromagnetic Transients Program' (ATP/EMTP). The influences of three parameters are considered: inception angles, the phase of the conductor, and the position at which the lightning struck the transmission system. By performing an operation scheme for all techniques, a positive sequence current is calculated, using a three-phase current from the ATP/EMTP program which is converted using Clark's transform. A positive sequence current is extracted to several scales using the DWT, and the orders of arrival times for both substations are determined. After the arrival times are obtained, each technique uses a different order of arrival time for calculating the lightning location. By comparing the average error among the three techniques, it is shown that the arrival time of the two sensors' technique is less than that of the other techniques.
Keywords: Discrete wavelet transforms; lightning location; lightning protection; power system transients; transmission lines; travelling wave